Profil Bioaktif Madu Lebah Tak Bersengat Berdasarkan Jenis Sumber Nektar - Bahar, Irnayanti; Astuti, Wiwik Wiji; Suhri, Andi Gita Maulidyah Indraswari (Berkala Ilmiah Biologi, 2025)
Stingless bee honey (Meliponini) is a natural product with strategic value in the functional food and health industries due to its unique bioactive compound content. However, variations in honey composition based on nectar sources in Indonesia, have not been thoroughly documented. This study aims to analyze the differences in moisture content, total sugars, polyphenols, antioxidant activity, and antimicrobial properties of stingless bee honey derived from different nectar sources. Honey samples were obtained from three distinct vegetative sources: acacia, rambutan, and longan nectars. Laboratory analyses were conducted using standard methods, including spectrophotometry for measuring sugar and polyphenol contents, DPPH assay for antioxidant activity, and disc diffusion method for antimicrobial testing. The results showed that honey from rambutan nectar had the lowest moisture content (23.5% ±1.2), the highest polyphenol content (356 ±21 mg GAE/100g), and the strongest antioxidant activity (IC50 12.4 mg/mL). In addition, this honey also demonstrated antimicrobial activity against Staphylococcus aureus with an inhibition zone of 14.2 ±1.5 mm. These findings indicate that nectar source plays a crucial role in determining honey quality, and may serve as a foundation for the development of high-value honey products based on local floral biodiversity.